E-governance in Africa: governing the continent through AU and Nepad websites - Mukhudwana, Rofhiwa Felicia (My University, 2008)
Africa’s way forward requires integration, democracy, good governance, participation and inclusive communication of all issues. Intergovernmental organizations are essential to facilitate the above mentioned goals. New thinking highlights the role of new media especially the Internet in democracy and governance in Africa. Therefore, the question solicited here is whether e-governance facilitates continental governance in Africa and under what circumstances would this be possible? This research introduced the internet (web) as a distinct medium of communications with distinct features and characteristics. A number of scholars argue that the Internet as a distinct medium of communication can better facilitate the democratizing role of the media in society, while others argues that the internet has not changed the nature of politics since ordinary politics in all its complexity and vitality has invaded and captured cyberspace. These arguments are divided respectively between Technological Determinism and the Social Shaping of Technology. This research investigates (AU, EU and Nepad) e-governance websites in order to understand practices, prospects and challenges of continental e-governance systems. It was found that the AU and Nepad use the websites for institutional information rather than interaction with citizens and online service delivery. However, significant steps are taken to enhance interaction in Nepad. It is therefore recommended that, the AU and Nepad need to invest time and commitment in enhancing interactivity and rising awareness for these e-governance systems. As projected, EU performs much better than the above two in terms of interactivity. This is because it has more experience and internet penetration and uses is widespread in Europe than it is here in Africa.
Keywords: New media; E-governance; E-politics; Internet; Websites; Technological determinism; Social shaping of technology; Interactivity; Nepad; African Union; European Union